The Master’s Perception of Maritime Safety - Mauritzson, Björn (My University, 2012)
This thesis is intended as an explorative study of Swedish masters’ perception of the concept of maritime safety, how to improve and maintain it and their, as well as other interested parties, role in relation to this. Ten active shipmasters were interviewed and their statements on this subject were analyzed and compared to previous research in the field. The results showed that Swedish masters assign a high priority to the safety of their vessel and those onboard it. Safety was in turn defined as the activity of ensuring that accidents are avoided. A high level of safety was furthermore believed to require safe behavior, entailing both rule adherence and safety initiatives. Such safe behavior was thought to be promoted through: informing individuals of the inherent risks involved in operations; monitoring activities and providing corrections; committed and supportive superiors who convey an impression of safety being important; involvement and participation in safety related activities and; good interpersonal relations in a non-hierarchical organization with a no-blame culture. There were also indications that maritime safety management is in danger of becoming excessively formalized, that some rules and procedures are believed to be ill-advised or impractical to adhere to and that there is a certain degree of confusion on how to deal with conflicts of interest involving safety.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering